(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we have conducted parametric analysis on the dynamics of satellite complex system using bifurcation theory. At first, five equilibrium points ε_0,1,2,3,4 are symbolically computed in which ε_1,3 and ε_2,4 are symmetric. Then, several theorems are stated and proved for the existence of B-T bifurcation on all equilibrium points with the aid of generalized eigenvectors and practical formulae instead of linearizations. Moreover, a special case α_2 = 0 is observed, which confirms all the discussed cases belong to a codimension-three bifurcation along with degeneracy conditions.